2018
DOI: 10.22159/ijap.2018.v10s1.27
|View full text |Cite
|
Sign up to set email alerts
|

Arginase Inhibitory Activity of Stem Bark Extracts of Caesalpinia Tortuosa Roxb

Abstract: Objective: This study aimed to evaluate the arginase inhibitory activity of Caesalpinia tortuosa Roxb. stem bark extracts.Methods: C. tortuosa Roxb. stem bark extracts were obtained through reflux extraction using n-hexane, ethyl acetate, and methanol and their inhibitory activity against arginase was measured using a microplate reader at 430 nm. Active extracts were subjected to phytochemical analysis and based on the qualitative phytochemical analysis, quantitative data regarding flavonoid and phenolic conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…This extract also have a high of total phenols and total flavonoids and this result as the same as our previous study. In the recent study the stem bark of Caesalpinia turtuosa has the arginase activity with the IC 50 11.58 μg/ml for methanol extract and 33.81 μg/ml for ethyl acetate extract; this result was the same as our study (Najid et al, 2018). a methanol extract of Sterculia comosa wood has the arginase inhibitory activity with IC 50 value of 2,787 μg/ml and high phenol content of 723.61 mgGAE/g.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This extract also have a high of total phenols and total flavonoids and this result as the same as our previous study. In the recent study the stem bark of Caesalpinia turtuosa has the arginase activity with the IC 50 11.58 μg/ml for methanol extract and 33.81 μg/ml for ethyl acetate extract; this result was the same as our study (Najid et al, 2018). a methanol extract of Sterculia comosa wood has the arginase inhibitory activity with IC 50 value of 2,787 μg/ml and high phenol content of 723.61 mgGAE/g.…”
Section: Discussionsupporting
confidence: 88%
“…In the recent study the stem bark of Caesalpinia turtuosa has the arginase activity with the IC 50 11.58 μg/ml for methanol extract and 33.81 μg/ml for ethyl acetate extract; this result was the same as our study. ( Najid et al 2018 ) a methanol extract of Sterculia comosa wood has the arginase inhibitory activity with IC 50 value of 2,787 μg/ml and high phenol content of 723.61 mgGAE /g. It is possible for the phenol compounds contained in this extract to contribute to inhibiting arginase activity.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This method was chosen because the sample used is the bark of the pepolo, which has a hard texture and is resistant to heat. 14 The resulting stem bark extract of pepolo was tested through phytochemical screening to identify its compounds. The results showed that pepolo stem bark extract contains flavonoid compounds, saponins, alkaloids, triterpenoids, and tannins.…”
Section: Discussionmentioning
confidence: 99%